Targeted Printing of Cells: Evaluation of ADA-PEG Bioinks for Drop on Demand Approaches - Karakaya, Emine; Bider, Faina; Frank, Andreas; Teßmar, Jörg; Schöbel, Lisa; Forster, Leonard; Schrüfer, Stefan; Schmidt, Hans-Werner; Schubert, Dirk W.; Blaeser, Andreas; Boccaccini, Aldo R.; Detsch, Rainer (Gels, 2022)
A novel approach, in the context of bioprinting, is the targeted printing of a defined number of cells at desired positions in predefined locations, which thereby opens up new perspectives for life science engineering. One major challenge in this application is to realize the targeted printing of cells onto a gel substrate with high cell survival rates in advanced bioinks. For this purpose, different alginate-dialdehyde—polyethylene glycol (ADA-PEG) inks with different PEG modifications and chain lengths (1–8 kDa) were characterized to evaluate their application as bioinks for drop on demand (DoD) printing. The biochemical properties of the inks, printing process, NIH/3T3 fibroblast cell distribution within a droplet and shear forces during printing were analyzed. Finally, different hydrogels were evaluated as a printing substrate. By analysing different PEG chain lengths with covalently crosslinked and non-crosslinked ADA-PEG inks, it was shown that the influence of Schiff’s bases on the viscosity of the corresponding materials is very low. Furthermore, it was shown that longer polymer chains resulted in less stable hydrogels, leading to fast degradation rates. Several bioinks highly exhibit biocompatibility, while the calculated nozzle shear stress increased from approx. 1.3 and 2.3 kPa. Moreover, we determined the number of cells for printed droplets depending on the initial cell concentration, which is crucially needed for targeted cell printing approaches.<br
Keywords: bioprinting; drop on demand; sodium alginate; polyethylene glycol; shear stress